THE PRACTICE OF SECULARISM IN RELIGIOUS CENCORSHIP IN TURKISH FILM (1939-1990) - Aditama, Aditama; Rachmanti, Nadira Bella; Soekarba, Siti Rohmah (UI Scholars Hub, 2019)
This paper analyzes a film as one of the media with the ability to convey certain messages to the public. Films can reflect the social and cultural conditions of society, thereby they can be used to spread the current ideas, views, and ideologies of a country. Films in Turkey are part of a culture that has developed rapidly and has become an entertainment for the people. Mustafa Kemal Atatürk reformed and turned Turkey into a new country with the ideology of secularism, controlling religious institutions and expressions. This journal article aims to describe the implementation of Turkish secular ideology in the country's cultural settings, namely censorship of religious elements in Turkish films from 1939 to 1990. The method used in this article is critical descriptive through literature study. This article concludes that censorship is not only practiced to maintain secularism in Turkey, but also to protect the religion itself.